Criminal Justice Students' Attitudes Toward LGBTQ Individuals and LGBTQ Police Officers. Issue 2 (3rd April 2019) - Tucker, Jane M.; Brewster, Mary P.; Grugan, Shannon T.; Miller, Lisa M.; Mapp-Matthews, Sadeiah M.
Abstract : Despite increasing acceptance of LGBTQ individuals in America, homophobia and homophobic attitudes among police officers are still a concern. Both LGBTQ individuals and LGBTQ officers report harassment and discrimination at the hands of police officers. Empirical evidence suggests that these homophobic attitudes are evident among students preparing for criminal justice careers. A number of studies have found that those who plan on law enforcement careers are significantly more homophobic. The current study sought to explore criminal justice students' attitudes toward LGBTQ individual and LGBTQ police officers. Pursuant to a survey of criminal justice majors at a large public university, findings suggest that males pursuing a law enforcement track expressed the most homophobia and homophobic attitudes. Further statistical analysis indicated that gender, not the law enforcement track, predicts homophobia and homophobic attitudes.